Electroterapia en equinos: uso de la electroestimulación mecánica por acción refleja (E.M.A.R.) en el síndrome podotroclear - García Liñeiro, J.A. (2007)
Mechanical Electrostimulation by Refl ex Action (R.A.M.E) acts by the application of low intensity exponential galvanic current for very short periods of time. Seventeen horses affected by Podothroclear syndrome were used in this experiencie in order to evaluate its effects as pain reliever. The horses were divided in two groups (13 horses with treatment) and group 2 (4 control horses). The diagnostic protocol used to diagnose all the cases consist on: a) lame degree, b) response to flexion test, and c) response to hoof tester. The treatment was applied twice daily for 12 days, and the horses were checked in order to evaluate the evolution. A proportions statistical analysis was performed using the Z statistical method, after having described the data obtained by lameness and flexion tests. At a level of 5%, we can assume that there was a significant clinical improvement in the treatment group, and hoof tester palpation results also improved. The control group hadn´t significant change in clini-cal signs between the start and end of the study. Therefore, it can be assumed that R.A.M.E. is a valid therapeutic tool in the management of chronic pain caused by navicular syndrome in the horse.